Method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries

Through the selective excellent dissolution and neutralization precipitation process, the problems of resource waste and impurity pollution in lithium iron phosphate battery recycling are solved, and efficient recycling of iron phosphate and lithium is achieved, simplifying the process flow and reducing costs.

CN119191320APending Publication Date: 2024-12-27GANZHOU CYCLEWELL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411691103.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery recycling process has problems such as waste of resources, high costs, impurity pollution and long production processes. It is difficult to effectively recover phosphorus and iron elements, and it is impossible to take into account the effective removal of copper and aluminum impurities and the complete leaching of iron and phosphorus.

Method used

The entire component dissolution of phosphorus, iron and lithium is achieved by controlling the reaction potential and pH through concentrated sulfuric acid, sodium sulfite and sodium dihydrogen phosphate. , and battery-grade iron phosphate was obtained by precipitation of hydrogen peroxide, and then the pH value was adjusted to crystallize lithium carbonate to reduce acid and base consumption and energy consumption.

Benefits of technology

The comprehensive recycling and utilization of iron phosphate and lithium are achieved, with short process flow and low production costs, which improves resource recovery rate and product purity, reduces energy consumption and impurity pollution, and simplifies the process route.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191320A_ABST
    Figure CN119191320A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing battery-grade iron phosphate and lithium carbonate from a waste lithium iron phosphate battery, and belongs to the technical field of lithium batteries, the method comprises the following steps: slurrying a waste lithium iron phosphate positive electrode material, adding concentrated sulfuric acid for leaching, adding sodium sulfite, controlling reaction potential, and carrying out filter pressing after reaction to obtain a leachate; iron is added into the leachate to remove copper, and copper-removed liquid and copper slag are obtained after filter pressing; adding sodium dihydrogen phosphate into the copper-removed liquid to remove aluminum, and carrying out filter pressing to obtain aluminum slag and impurity-removed liquid; adjusting the pH value of the impurity-removed solution, adding hydrogen peroxide, reacting to obtain an iron phosphate dehydrate precipitate and an iron phosphate mother solution, and treating the iron phosphate dehydrate to obtain battery-grade anhydrous iron phosphate; adjusting the pH value of the iron phosphate mother liquor, carrying out filter pressing to obtain impurity-removed slag and a lithium sulfate solution, adding sodium carbonate into the lithium sulfate solution, carrying out heating reaction, filtering slurry to obtain a lithium carbonate wet material, and treating to obtain battery-grade lithium carbonate. According to the method, the problem of recycling the waste lithium iron phosphate battery material iron phosphate is solved, and comprehensive recycling of the iron phosphate and the lithium material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries. Background Art

[0002] Lithium-ion batteries are increasingly used in daily life, so the recycling of lithium-ion batteries has become an issue that cannot be ignored. The positive electrode, negative electrode, and electrolyte in lithium-ion batteries all need to be recycled and reused, and the recycling of positive electrode materials is an important link in the lithium-ion battery recycling industry. Currently, commonly used positive electrode materials include lithium iron phosphate and ternary lithium. The current conventional lithium iron phosphate recycling method is to recover the high-value lithium through oxidative acid leaching. The phosphorus and iron elements in the ferrophosphorus slag cannot be well recovered, resulting in serious waste of resources and the problem of secondary pollution.

[0003] The general method of recovering iron phosphate is to dissolve the iron phosphate with a high concentration of inorganic acid such as sulfuric acid, phosphoric acid or a mixed acid, and then add sodium hydroxide or ammonia water to the leachate to adjust the pH to precipitate the iron phosphate. Obviously, a large amount of acid and alkali need to be used in this method, which has the problems of high cost and low economic benefit, and the recovery rate of iron and phosphorus resources is low. In addition, in the process of extracting iron phosphate, part of the copper and aluminum will flow into the iron phosphate product, resulting in a decrease in product purity, and the phosphorus loss rate of the existing copper and aluminum removal technology is high, so it is impossible to take into account the effective removal of copper and aluminum impurities and the complete leaching and recovery of iron and phosphorus elements. In addition, in the traditional iron phosphate crystallization process, it is necessary to combine oxidation crystallization and aging crystallization under high temperature conditions to reduce the entrainment and coating of sulfate and sodium elements. This process has high energy consumption and a long production process.

[0004] It can be seen that there is still a lot of room for optimization in the current process of recycling and reusing lithium iron phosphate, and it is necessary to propose a new process. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries, which solves the problem of recycling iron phosphate of waste lithium iron phosphate battery materials and realizes the comprehensive recycling of iron phosphate and lithium materials, and has the advantages of short process flow and low production cost.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries, comprising:

[0008] (1) Slurrying the waste lithium iron phosphate positive electrode material, adding concentrated sulfuric acid for leaching, and then adding sodium sulfite, controlling the reaction potential in the solution to be 200-350 mV, and filtering after the reaction to obtain a leachate and graphite slag;

[0009] (2) adding iron to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0010] (3) adding sodium dihydrogen phosphate to the copper removal solution to remove aluminum in the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0011] (4) adjusting the pH of the impurity-removed solution to 1.0-3.0, adding hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0012] (5) adjusting the pH of the iron phosphate mother liquor to 8-12, filtering to obtain impurity-removing residue and lithium sulfate solution, adding sodium carbonate to the lithium sulfate solution, heating to react to obtain a slurry containing lithium carbonate, filtering the slurry to obtain a lithium carbonate wet material and a lithium carbonate mother liquor, washing the lithium carbonate wet material and drying it to obtain battery-grade lithium carbonate.

[0013] Preferably, in step (1), the amount of concentrated sulfuric acid added is 0.5 to 2.5 times the lithium content in the waste lithium iron phosphate positive electrode material, calculated by molar ratio. More preferably, the amount of concentrated sulfuric acid added is 1 to 2.5 times the lithium content in the waste lithium iron phosphate positive electrode material.

[0014] Preferably, calculated on a molar basis, the amount of sodium sulfite added is 1 to 3 times the content of trivalent iron in the waste lithium iron phosphate positive electrode material.

[0015] Preferably, in step (2), the amount of iron added is 1 to 3.5 times the theoretical content of copper in the leaching solution, calculated on a molar basis.

[0016] Preferably, in step (3), calculated by molar ratio, the amount of sodium dihydrogen phosphate added is 1 to 3.5 times the aluminum content in the copper removal solution. Preferably, the amount of sodium dihydrogen phosphate added is 1 to 3 times the aluminum content in the copper removal solution.

[0017] Preferably, in step (4), the iron-phosphorus content in the impurity-removed liquid is adjusted to control the molar ratio of iron-phosphorus to (0.95-1.1):1.

[0018] Preferably, in step (4), the amount of hydrogen peroxide in the hydrogen peroxide is 0.5 to 1.5 times the iron content in the impurity-removed liquid in terms of molar ratio. Preferably, the mass fraction of the hydrogen peroxide is 25 to 30%, and more preferably, the mass fraction of the hydrogen peroxide is 27.5%.

[0019] Preferably, in step (5), sodium carbonate is added to the lithium sulfate solution, and the amount of sodium carbonate used is 0.5 to 1.25 times the lithium content in the lithium sulfate, calculated on a molar ratio.

[0020] Preferably, in step (5), the lithium carbonate mother liquor is evaporated and crystallized, the concentrated slurry is filtered to obtain a lithium solution and sodium sulfate, sodium carbonate is added to the lithium solution for secondary lithium carbonate crystallization to obtain lithium carbonate and a lithium carbonate mother liquor, the lithium carbonate obtained by the secondary crystallization is combined with the lithium carbonate wet material for washing, and the lithium carbonate mother liquor is mixed with the lithium carbonate mother liquor after centrifugal filtration and evaporated and crystallized again.

[0021] Preferably, in step (4) and step (5), liquid alkali is added to adjust the pH value.

[0022] Beneficial Effects

[0023] The present invention adopts a selective optimal dissolution + impurity removal + neutralization precipitation + one-step precipitation process to achieve the dissolution of all components of phosphorus, iron and lithium metals. At the same time, by adjusting the point control agent in the selective optimal dissolution stage, the selective inhibition of impurity ions such as aluminum and titanium can be achieved, thereby improving the purity of the solution, reducing the impurity removal cost, and shortening the process route.

[0024] The present invention realizes the effective recovery of difficult-to-treat iron phosphate slag, and can cyclically prepare battery-grade iron phosphate materials. Compared with the traditional process, the acid and alkali consumption of the process of the present invention is low. Through potential regulation, the leaching of impurity materials is effectively suppressed, and the coating problem of sulfate and sodium ions in the product crystallization process is solved, so that battery-grade iron phosphate is obtained by one-step crystallization, and impurities and insoluble graphite carbon slag in the battery material are treated as solid waste, thereby reducing production costs; after neutralizing and precipitating the iron phosphate, further adsorption and impurity removal can be performed to obtain a pure lithium sulfate solution, and then sodium carbonate is added to perform a crystallization reaction to obtain battery-grade lithium carbonate, which can be used in the preparation of positive electrode materials for lithium-ion batteries.

[0025] The invention solves the problem of recycling iron phosphate of waste lithium iron phosphate battery materials and realizes the comprehensive recycling of iron phosphate and lithium materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0028] like Figure 1 As shown, the present invention provides a method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries, comprising the following steps:

[0029] (1) slurrying the waste lithium iron phosphate positive electrode material, adding concentrated sulfuric acid for leaching, then adding sodium sulfite, and filtering after reaction to obtain a leachate and graphite slag;

[0030] (2) adding iron to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0031] (3) adding sodium dihydrogen phosphate to the copper removal solution to remove aluminum in the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0032] (4) adjusting the pH of the impurity-removed solution to 1.0-3.0, adding hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0033] (5) adjusting the pH of the iron phosphate mother liquor to 8-12, preferably to 11, filtering to obtain impurity-removing residue and lithium sulfate solution, adding sodium carbonate to the lithium sulfate solution, heating to react to obtain a slurry containing lithium carbonate, filtering the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, washing the wet lithium carbonate and drying it to obtain battery-grade lithium carbonate.

[0034] In step (1), when the waste lithium iron phosphate positive electrode material is slurried, the liquid-to-solid mass ratio is controlled to be (3-6):1. Calculated by molar ratio, the amount of concentrated sulfuric acid added is 0.5-2.5 times the lithium content in the waste lithium iron phosphate positive electrode material, preferably 1-2.5 times, and the amount of sodium sulfite added is 1-3 times the trivalent iron content in the waste lithium iron phosphate positive electrode material.

[0035] In step (1), after adding sodium sulfite, the reaction potential in the solution is controlled to be 200-350 mV, the reaction temperature is 40-70° C., and the reaction time is 2-6 hours.

[0036] The purpose of controlling the reaction potential and adding sodium sulfite is to inhibit the leaching of titanium and aluminum in the waste lithium iron phosphate positive electrode material, so that part of the aluminum and titanium exist in the graphite slag in the form of precipitation, reduce the back-end impurity removal cost and lithium metal loss, and improve economic benefits.

[0037] The iron phosphate process adopts the method of adsorption impurity remover + Zeta potential regulator to reduce the coating of sulfate and sodium ions, reduce the crystallization process in the aging stage, realize the one-step crystallization synthesis of iron phosphate process, and reduce energy consumption.

[0038] In step (1), the graphite slag obtained by filter pressing is washed, and the liquid-to-solid ratio during the washing process is (5-10):1. Then, filter pressing is performed to recover the graphite slag obtained by filter pressing, such as outsourcing the graphite slag for treatment, and the washing water is returned to the system for use.

[0039] In step (2), the amount of iron added is 1 to 3.5 times the theoretical content of copper in the leaching solution, calculated by molar ratio, and the iron replaces the copper in the solution. The reaction temperature is controlled at 40 to 70° C. and the reaction time is 1 to 4 hours.

[0040] In step (2), the copper slag obtained by filter pressing is washed, and the liquid-to-solid ratio during the washing process is (5-10):1. Then, sponge copper and washing water are obtained by filter pressing. The washing water is returned to the system for use, and the sponge copper is exported for processing.

[0041] In step (3), the amount of sodium dihydrogen phosphate added is 1 to 3.5 times, more preferably 1 to 3 times, the aluminum content in the copper removal solution, calculated by molar ratio, the reaction temperature is 40 to 70° C., and the reaction time is 2 to 6 hours.

[0042] In step (3), the aluminum slag obtained by filter pressing is washed, and the liquid-to-solid ratio during the washing process is (5-10):1. The aluminum slag after filter pressing is outsourced for treatment, and the washing water is returned to the system for use.

[0043] In step (4), the iron-phosphorus content in the impurity-removed liquid is adjusted to control the molar ratio of iron to phosphorus to (0.95-1.1):1, liquid caustic soda is added to control the pH value of the impurity-removed liquid to 1.0-3.0, and then hydrogen peroxide is added. Calculated by molar ratio, the amount of hydrogen peroxide in the hydrogen peroxide is 0.5-1.5 times the iron content in the impurity-removed liquid, the reaction temperature is controlled to 70-100° C., and the reaction time is 2-6 hours.

[0044] Preferably, the mass fraction of hydrogen peroxide is 25-30%, and more preferably, the mass fraction of hydrogen peroxide is 27.5%.

[0045] The addition of hydrogen peroxide and liquid alkali, as well as the control of the stirring crystallization process, can reduce the coating of sodium and sulfate in the ferric phosphate crystals and improve the quality of the ferric phosphate product.

[0046] In step (4), the ferric phosphate dihydrate obtained after the reaction is washed, and the liquid-to-solid ratio during the washing process is (10-30):1, and then the ferric phosphate dihydrate is filtered, and the washing water is returned to the system for use. The wet ferric phosphate dihydrate is dried and then roasted for dehydration. The roasting time is 2-4 hours and the roasting temperature is 500-800°C to obtain battery-grade anhydrous ferric phosphate.

[0047] In step (5), liquid caustic soda is added to the iron phosphate mother liquor to adjust the pH value to 11, so that the iron and other impurity elements in the solution are completely precipitated, and the impurity-removing slag and lithium sulfate solution are obtained after pressure filtration. Sodium carbonate is added to the lithium sulfate solution, and the amount of sodium carbonate used is 0.5 to 1.25 times the lithium content in the lithium sulfate in terms of molar ratio. The reaction temperature is controlled to be 70 to 100° C., and the reaction time is 2 to 6 hours. After a period of temperature reaction, lithium carbonate slurry is obtained, and lithium carbonate is slightly soluble. The lithium carbonate slurry is centrifuged and filtered to obtain lithium carbonate wet material and lithium carbonate mother liquor.

[0048] The wet lithium carbonate is washed and then dried at a temperature of 150 to 300° C. The wet lithium carbonate is completely dried. Preferably, the drying time is 2 hours.

[0049] Furthermore, the lithium carbonate mother liquor is evaporated and crystallized, and the concentrated slurry is filtered to obtain a lithium solution and sodium sulfate. Sodium carbonate is added to the lithium solution for secondary lithium carbonate crystallization to obtain lithium carbonate and a lithium carbonate mother liquor. The lithium carbonate and the lithium carbonate wet material are combined for washing, and the lithium carbonate mother liquor is mixed with the lithium carbonate mother liquor after centrifugal filtration and evaporated and crystallized again.

[0050] The present invention effectively recovers metals such as phosphorus, iron, copper, and lithium from waste lithium iron phosphate positive electrode materials, and ultimately obtains battery-grade iron phosphate and lithium carbonate products, which can be directly used in the preparation of precursor materials for lithium iron phosphate battery materials. During the preparation process, the washing water of the present invention can be returned to the system for recycling, achieving zero discharge of production wastewater.

[0051] The technical solution of the present invention is described in detail below with specific embodiments.

[0052] Example 1

[0053] A batch of waste lithium iron phosphate positive electrode powder was selected, and the test results of the powder are shown in Table 1 below:

[0054] Table 1 Detection components of waste lithium iron phosphate positive electrode powder

[0055] Detection elements Element content (%) P 18 Fe 38 Li 4.02 Cu 1.02 Al 0.57 <![CDATA[Fe 3+ ]]> 3

[0056] (1) 1000 g of the batch of waste lithium iron phosphate positive electrode materials was added to 5000 ml of pure water for slurrying, 740 g of concentrated sulfuric acid was added for leaching, and 70 g of sodium sulfite was added, the reaction potential in the solution was controlled to be 200 mV, and after the reaction, 4600 ml of leachate and graphite slag were obtained by filter pressing;

[0057] (2) adding 20 g of iron powder to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0058] (3) adding 80 g of sodium dihydrogen phosphate to the copper removal solution to remove aluminum from the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0059] (4) adding 200 g of liquid caustic soda to the impurity-removed liquid to adjust the pH of the impurity-removed liquid to 2.0, adding 800 g of hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0060] (5) Add 540 g of liquid caustic soda to the iron phosphate mother liquor, adjust the pH value of the iron phosphate mother liquor to 9, filter press to obtain impurity-removing residue and lithium sulfate solution, add 400 g of sodium carbonate to the lithium sulfate solution, heat the reaction to obtain a slurry containing lithium carbonate, filter the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, wash the wet lithium carbonate and dry it to obtain battery-grade lithium carbonate.

[0061] The data of the produced anhydrous iron phosphate and lithium carbonate after testing and analysis are shown in Tables 2 and 3 below:

[0062] Table 2 Ferric phosphate product data Test items Standard value Product test value Fe / % 36.0-36.85 36.02 P / % 20.30-21.1 20.4 Fe / P 0.960-0.985 0.98 Mn / % ≤0.1 0.021 Cu / % ≤0.001 0.00015 Zn / % ≤0.002 0.001 Cd / % ≤0.005 0.001 Ca / % ≤0.008 0.0005 Mg / % ≤0.005 0.0008 Cr / % ≤0.005 0.0028 Na / % ≤0.02 0.023 Al / % ≤0.01 0.0005 K / % ≤0.050 / Co / % ≤0.005 0.0045 Ni / % ≤0.005 0.0047 Ti / % ≤0.02 0.017 S / % ≤0.02 0.013

[0063] Wherein, P / Fe refers to the molar ratio of iron content to phosphorus content, the same below.

[0064] Table 3 Lithium carbonate product data

[0065] Test items Standard value Product test value <![CDATA[Li2CO3 content]]> ≥99.2% 99.3% Na / % ≤0.08 0.04 Mg / % ≤0.015 0.013 Ca / % ≤0.025 0.022 K / % / / Fe / % ≤0.002 0.0010 Zn / % / / Cu / % / / Pb / % / / Si / % / / Al / % / / Mn / % / / Ni / % / / B / % / / <![CDATA[SO4 2- / %]]> ≤0.2 0.18 <![CDATA[Cl - / %]]> ≤0.01 0.00012 Hydrochloric acid insoluble matter / % ≤0.005 0.004

[0066] Example 2

[0067] A batch of waste lithium iron phosphate positive electrode powder was selected, and the test results of the powder are shown in Table 4 below:

[0068] Table 4 Detection components of waste lithium iron phosphate positive electrode powder

[0069] Detection elements Element content (%) P 18 Fe 38 Li 4.02 Cu 1.02 Al 0.57 <![CDATA[Fe 3+ ]]> 3

[0070] (1) 1000 g of the batch of waste lithium iron phosphate positive electrode materials was added to 5000 ml of pure water for slurrying, 740 g of concentrated sulfuric acid was added for leaching, and 70 g of sodium sulfite was added, the reaction potential in the solution was controlled to be 200 mV, and after the reaction, 4600 ml of leachate and graphite slag were obtained by filter pressing;

[0071] (2) adding 20 g of iron powder to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0072] (3) adding 80 g of sodium dihydrogen phosphate to the copper removal solution to remove aluminum from the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0073] (4) adding 200 g of liquid caustic soda to the impurity-removed liquid to adjust the pH of the impurity-removed liquid to 2.0, adding 800 g of hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0074] (5) Add 620 g of liquid caustic soda to the iron phosphate mother liquor, adjust the pH value of the iron phosphate mother liquor to 11, filter press to obtain impurity-removing residue and lithium sulfate solution, add 400 g of sodium carbonate to the lithium sulfate solution, heat the reaction to obtain a slurry containing lithium carbonate, filter the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, wash the wet lithium carbonate and dry it to obtain battery-grade lithium carbonate.

[0075] The data of the produced anhydrous iron phosphate and lithium carbonate after testing and analysis are as follows Tables 5 and 6:

[0076] Table 5 Iron phosphate product data

[0077] Test items Standard value Product test value Fe / % 36.0-36.85 36.01 P / % 20.30-21.1 20.3 Fe / P 0.960-0.985 0.98 Mn / % ≤0.1 0.022 Cu / % ≤0.001 0.0002 Zn / % ≤0.002 0.0015 Cd / % ≤0.005 0.002 Ca / % ≤0.008 0.0008 Mg / % ≤0.005 0.002 Cr / % ≤0.005 0.004 Na / % ≤0.02 0.015 Al / % ≤0.01 0.0008 K / % ≤0.050 / Co / % ≤0.005 0.0044 Ni / % ≤0.005 0.0041 Ti / % ≤0.02 0.014 S / % ≤0.02 0.016

[0078] Table 6 Lithium carbonate product data

[0079] Test items Standard value Product test value <![CDATA[Li2CO3 content]]> ≥99.2% 99.3% Na / % ≤0.08 0.07 Mg / % ≤0.015 0.012 Ca / % ≤0.025 0.020 K / % / / Fe / % ≤0.002 0.0012 Zn / % / / Cu / % / / Pb / % / / Si / % / / Al / % / / Mn / % / / Ni / % / / B / % / / <![CDATA[SO4 2- / %]]> ≤0.2 0.15 <![CDATA[Cl - / %]]> ≤0.01 0.00013 Hydrochloric acid insoluble matter / % ≤0.005 0.0035

[0080] Example 3

[0081] A batch of waste lithium iron phosphate positive electrode powder was selected, and the test results of the powder are shown in Table 7 below:

[0082] Table 7 Detection components of waste lithium iron phosphate positive electrode powder

[0083] Detection elements Element content (%) P 18 Fe 38 Li 4.02 Cu 1.02 Al 0.57 <![CDATA[Fe 3+ ]]> 3

[0084] (1) 1000 g of waste lithium iron phosphate positive electrode material was added to 5000 ml of pure water for slurrying, 740 g of concentrated sulfuric acid was added for leaching, and 67 g of sodium sulfite was added, the reaction potential in the solution was controlled to be 300 mV, and after the reaction, 4600 ml of leachate and graphite slag were obtained by filter pressing;

[0085] (2) adding 20 g of iron powder to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0086] (3) adding 80 g of sodium dihydrogen phosphate to the copper removal solution to remove aluminum from the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0087] (4) adding 280 g of liquid alkali to the impurity-removed liquid, adjusting the pH value of the impurity-removed liquid to 3.0, adding 800 g of hydrogen peroxide, reacting to obtain a dihydrate iron phosphate precipitate and an iron phosphate mother liquor, washing the dihydrate iron phosphate, drying, roasting and dehydrating it to obtain a battery-grade anhydrous iron phosphate;

[0088] (5) Add 550 g of liquid alkali to the iron phosphate mother liquor, adjust the pH value of the iron phosphate mother liquor to 11, filter press to obtain impurity-removing residue and lithium sulfate solution, add 400 g of sodium carbonate to the lithium sulfate solution, heat the reaction to obtain a slurry containing lithium carbonate, filter the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, wash the wet lithium carbonate and dry it to obtain battery-grade lithium carbonate.

[0089] The data of the produced anhydrous iron phosphate and lithium carbonate after testing and analysis are shown in Tables 8 and 9 below:

[0090] Table 8 Ferric phosphate product data

[0091] Test items Standard value Product test value Fe / % 36.0-36.85 36.5 P / % 20.30-21.1 20.7 Fe / P 0.960-0.985 0.98 Mn / % ≤0.1 0.025 Cu / % ≤0.001 0.00015 Zn / % ≤0.002 0.0010 Cd / % ≤0.005 0.0015 Ca / % ≤0.008 0.0005 Mg / % ≤0.005 0.0002 Cr / % ≤0.005 0.0028 Na / % ≤0.02 0.017 Al / % ≤0.01 0.0006 K / % ≤0.050 / Co / % ≤0.005 0.0048 Ni / % ≤0.005 0.0045 Ti / % ≤0.02 0.010 S / % ≤0.02 0.014

[0092] Table 9 Lithium carbonate product data

[0093] Test items Standard value Product test value <![CDATA[Li2CO3 content]]> ≥99.2% 99.3% Na / % ≤0.08 0.06 Mg / % ≤0.015 0.007 Ca / % ≤0.025 0.019 K / % / / Fe / % ≤0.002 0.0013 Zn / % / / Cu / % / / Pb / % / / Si / % / / Al / % / / Mn / % / / Ni / % / / B / % / / <![CDATA[SO4 2- / %]]> ≤0.2 0.12 <![CDATA[Cl - / %]]> ≤0.01 0.00015 Hydrochloric acid insoluble matter / % ≤0.005 0.0028

[0094] Comparative Example 1

[0095] A batch of waste lithium iron phosphate positive electrode powder was selected, and the test results of the powder are shown in Table 10 below:

[0096] Table 10 Detection components of waste lithium iron phosphate positive electrode powder

[0097] Detection elements Element content (%) P 18 Fe 38 Li 4.02 Cu 1.02 Al 0.57 <![CDATA[Fe 3+ ]]> 3

[0098] (1) 1000 g of waste lithium iron phosphate positive electrode material was added to 5000 ml of pure water for slurrying, 740 g of concentrated sulfuric acid was added for leaching, and 100 g of sodium sulfite was added to control the reaction potential in the solution to be 150 mV. After the reaction, 4600 ml of leachate and graphite slag were obtained by filter pressing;

[0099] (2) adding 20 g of iron powder to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0100] (3) adding 80 g of sodium dihydrogen phosphate to the copper removal solution to remove aluminum from the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0101] (4) adding 100 g of liquid alkali to the impurity-removed liquid, adjusting the pH value of the impurity-removed liquid to 1.0, adding 800 g of hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0102] (5) Add 640 g of liquid caustic soda to the iron phosphate mother liquor, adjust the pH value of the iron phosphate mother liquor to 9, filter press to obtain impurity-removing residue and lithium sulfate solution, add 400 g of sodium carbonate to the lithium sulfate solution, heat the reaction to obtain a slurry containing lithium carbonate, filter the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, wash the wet lithium carbonate and dry it to obtain battery-grade lithium carbonate.

[0103] The data of the produced anhydrous iron phosphate and lithium carbonate after testing and analysis are as follows11 and 12:

[0104] Table 11 Ferric phosphate product data

[0105] Test items Standard value Product test value Fe / % 36.0-36.85 35.5 P / % 20.30-21.1 20.7 Fe / P 0.960-0.985 0.95 Mn / % ≤0.1 0.0202 Cu / % ≤0.001 0.0002 Zn / % ≤0.002 0.001 Cd / % ≤0.005 0.0023 Ca / % ≤0.008 0.00039 Mg / % ≤0.005 0.00058 Cr / % ≤0.005 0.00228 Na / % ≤0.02 0.01921 Al / % ≤0.01 0.00085 K / % ≤0.050 / Co / % ≤0.005 0.00451 Ni / % ≤0.005 0.00473 Ti / % ≤0.02 0.0135 S / % ≤0.02 0.0118

[0106] Table 12 Lithium carbonate product data

[0107] Test items Standard value Product test value <![CDATA[Li2CO3 content]]> ≥99.2% 99.3% Na / % ≤0.08 0.04 Mg / % ≤0.015 0.0111 Ca / % ≤0.025 0.0221 K / % / / Fe / % ≤0.002 0.0015 Zn / % / / Cu / % / / Pb / % / / Si / % / / Al / % / / Mn / % / / Ni / % / / B / % / / <![CDATA[SO4 2- / %]]> ≤0.2 0.168 <![CDATA[Cl - / %]]> ≤0.01 0.0021 Hydrochloric acid insoluble matter / % ≤0.005 0.0036

[0108] Comparative Example 2

[0109] A batch of waste lithium iron phosphate positive electrode powder was selected, and the test results of the powder are shown in Table 13 below:

[0110] Table 13 Detection components of waste lithium iron phosphate positive electrode powder

[0111] Detection elements Element content (%) P 18 Fe 38 Li 4.02 Cu 1.02 Al 0.57 <![CDATA[Fe 3+ ]]> 3

[0112] (1) 1000 g of waste lithium iron phosphate positive electrode material was added to 5000 ml of pure water for slurrying, 740 g of concentrated sulfuric acid was added for leaching, and 40 g of sodium sulfite was added to control the reaction potential in the solution to be 400 mV. After the reaction, 4600 ml of leachate and graphite slag were obtained by filter pressing;

[0113] (2) adding 20 g of iron powder to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing;

[0114] (3) adding 80 g of sodium dihydrogen phosphate to the copper removal solution to remove aluminum from the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing;

[0115] (4) adding 230 g of liquid caustic soda to the impurity-removed liquid to adjust the pH of the impurity-removed liquid to 3.5, adding 800 g of hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate;

[0116] (5) Add 590 g of liquid alkali to the iron phosphate mother liquor, adjust the pH value of the iron phosphate mother liquor to 11, filter press to obtain impurity-removing residue and lithium sulfate solution, add 400 g of sodium carbonate to the lithium sulfate solution, heat the reaction to obtain a slurry containing lithium carbonate, filter the slurry to obtain wet lithium carbonate and lithium carbonate mother liquor, wash the wet lithium carbonate and dry it to obtain battery-grade lithium carbonate.

[0117] The data of the produced anhydrous iron phosphate and lithium carbonate after testing and analysis are shown in Tables 14 and 15 below:

[0118] Table 14 Ferric phosphate product data

[0119] Test items Standard value Product test value Fe / % 36.0-36.85 37.22 P / % 20.30-21.1 19.99 Fe / P 0.960-0.985 1.03 Mn / % ≤0.1 0.026 Cu / % ≤0.001 0.0002 Zn / % ≤0.002 0.001 Cd / % ≤0.005 0.002 Ca / % ≤0.008 0.0006 Mg / % ≤0.005 0.0008 Cr / % ≤0.005 0.0024 Na / % ≤0.02 0.019 Al / % ≤0.01 0.0005 K / % ≤0.050 / Co / % ≤0.005 0.0051 Ni / % ≤0.005 0.0046 Ti / % ≤0.02 0.018 S / % ≤0.02 0.018

[0120] Table 15 Lithium carbonate product data

[0121] Test items Standard value Product test value <![CDATA[Li2CO3 content]]> ≥99.2% 99.3% Na / % ≤0.08 0.02 Mg / % ≤0.015 0.012 Ca / % ≤0.025 0.019 K / % / / Fe / % ≤0.002 0.0011 Zn / % / / Cu / % / / Pb / % / / Si / % / / Al / % / / Mn / % / / Ni / % / / B / % / / <![CDATA[SO4 2- / %]]> ≤0.2 0.13 <![CDATA[Cl - / %]]> ≤0.01 0.001 Hydrochloric acid insoluble matter / % ≤0.005 0.0026

[0122] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries, characterized in that: include: (1) Slurrying the waste lithium iron phosphate positive electrode material, adding concentrated sulfuric acid for leaching, and then adding sodium sulfite, controlling the reaction potential in the solution to be 200-350 mV, and filtering after the reaction to obtain a leachate and graphite slag; (2) adding iron to the leachate to remove copper from the leachate, and obtaining a copper removal solution and copper slag after filter pressing; (3) adding sodium dihydrogen phosphate to the copper removal solution to remove aluminum in the copper removal solution, and obtaining aluminum slag and impurity-removed liquid after filter pressing; (4) adjusting the pH of the impurity-removed solution to 1.0-3.0, adding hydrogen peroxide, reacting to obtain a dihydrate ferric phosphate precipitate and a ferric phosphate mother liquor, washing the dihydrate ferric phosphate, drying, roasting and dehydrating the ferric phosphate to obtain a battery-grade anhydrous ferric phosphate; (5) adjusting the pH of the iron phosphate mother liquor to 8-12, filtering to obtain impurity-removing residue and lithium sulfate solution, adding sodium carbonate to the lithium sulfate solution, heating to react to obtain a slurry containing lithium carbonate, filtering the slurry to obtain a lithium carbonate wet material and a lithium carbonate mother liquor, washing the lithium carbonate wet material and drying it to obtain battery-grade lithium carbonate.

2. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (1), the amount of concentrated sulfuric acid added is 0.5 to 2.5 times the lithium content in the waste lithium iron phosphate positive electrode material, calculated on a molar basis.

3. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: Calculated on a molar basis, the amount of sodium sulfite added is 1 to 3 times the content of trivalent iron in the waste lithium iron phosphate positive electrode material.

4. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (2), the amount of iron added is 1 to 3.5 times the theoretical content of copper in the leaching solution, calculated on a molar basis.

5. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (3), the amount of sodium dihydrogen phosphate added is 1 to 3.5 times the aluminum content in the copper removal solution, calculated on a molar basis.

6. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (4), the iron and phosphorus content in the impurity-removed liquid is adjusted to control the molar ratio of iron and phosphorus to (0.95-1.1):

1.

7. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (4), the amount of hydrogen peroxide added in the hydrogen peroxide is 0.5 to 1.5 times the iron content in the liquid after impurity removal, calculated in molar ratio.

8. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (5), sodium carbonate is added to the lithium sulfate solution, and the amount of sodium carbonate used is 0.5 to 1.25 times the lithium content of the lithium sulfate calculated by molar ratio.

9. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (5), the lithium carbonate mother liquor is evaporated and crystallized, and the concentrated slurry is filtered to obtain a lithium solution and sodium sulfate. Sodium carbonate is added to the lithium solution for secondary lithium carbonate crystallization to obtain lithium carbonate and a lithium carbonate mother liquor. The lithium carbonate obtained by the secondary crystallization is combined with the lithium carbonate wet material for washing, and the lithium carbonate mother liquor is mixed with the lithium carbonate mother liquor after centrifugal filtration and evaporated and crystallized again.

10. The method for preparing battery-grade iron phosphate and lithium carbonate from waste lithium iron phosphate batteries according to any one of claims 1 to 9, characterized in that: In step (4) and step (5), liquid alkali is added to adjust the pH value.

Citation Information

Patent Citations

  • Method for preparing lithium iron phosphate positive electrode material from waste lithium iron phosphate battery

    CN111009660A

  • Method for recovering and preparing battery-grade lithium carbonate and iron phosphate from positive electrode powder of waste lithium iron phosphate battery

    CN113912032A

  • Method for preparing iron phosphate from waste lithium iron phosphate batteries

    CN115057425A

  • Method for recycling battery-grade iron phosphate and lithium carbonate by using waste lithium iron phosphate battery material

    CN117776133A

  • Recovery method for lithium iron phosphate

    WO2024021237A1

Cited By

  • Method for recovering iron phosphate and lithium carbonate from lithium iron phosphate waste

    CN120041670A

  • A Method and Application for Recycling and Regenerating Lithium from Power Batteries

    CN120174204B

  • Method and system for recovering iron and lithium from waste lithium iron phosphate battery

    CN120527506A

  • Method for mildly, rapidly and selectively recycling lithium iron phosphate battery positive electrode material by wet process

    CN121642264A